Review article: novel oral‐targeted therapies in inflammatory bowel disease. Issue 12 (19th April 2018) - White, J. R.; Phillips, F.; Monaghan, T.; Fateen, W.; Samuel, S.; Ghosh, S.; Moran, G. W.
Summary: Background: There is a great unmet clinical need for efficacious, tolerable, economical and orally administrated drugs for the treatment of inflammatory bowel disease (IBD). New therapeutic avenues have become possible including the development of medications that target specific genetic pathways found to be relevant in other immune mediated diseases. Aims: To provide an overview of recent clinical trials for new generation oral targeted medications that may have a future role in IBD management. Methods: Pubmed and Medline searches were performed up to 1 March 2018 using keywords: "IBD", "UC", "CD", "inflammatory bowel disease" "ulcerative colitis", "Crohn's disease" in combination with "phase", "study", "trial" and "oral". A manual search of the clinical trial register, article reference lists, abstracts from meetings of Digestive Disease Week, United European Gastroenterology Week and ECCO congress were also conducted. Results: In randomised controlled trials primary efficacy endpoints were met for tofacitinib (JAK 1/3 inhibitor‐phase III), upadacitinib (JAK 1 inhibitor‐phase II) and AJM300 (α4‐integrin antagonist‐phase II) in ulcerative colitis. Ozanimod (S1P receptor agonist‐phase II) also demonstrated clinical remission. For Crohn's disease, filgotinib (JAK1 inhibitor‐phase II) met primary endpoints and laquinimod (quinolone‐3‐carboxide small molecule‐phase II) was also efficacious. Trials using mongersen (SMAD7 inhibitor) and vidofludimus (dihydroorotate dehydrogenase inhibitor) have been halted. Conclusions: This is potentially the start of an exciting new era in which multiple therapeutic options are at the disposal of physicians to treat IBD on an individualised basis. Head‐to‐head studies with existing treatments and longer term safety data are needed for this to be possible.